DAMPAK KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN RUMAH SAKIT (Analisis Pengukuran Kinerja NonKeuangan) - Erwin Saraswati; Dian Purnama Sari (Jurusan Akuntansi,Fakultas Bisnis dan Ekonomika,Universitas Surabaya, 2018)
Performance measurement in hospitals is difficult to do because the human resources did much in the operational activities. This study tried to analyze patient satisfaction as one of the non-financial measurement process quality of services performed by doctors, nurses and pharmacy staff. Results of this study showed that the quality of the service process by doctors, nurses and successfully treatment significantly influence patient satisfaction. This indicates that the quality of the service process by doctors, nurses and successfully treatment can be measured through patient satisfaction. Quality of the service process by pharmacy staff and ease adminitratif no significant effect on patient satisfaction. That is, there is the quality of the service process by pharmacy staff and ease adminitratif should be measured through the measurement of non-financial sharing.